2021
DOI: 10.1002/iid3.471
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac biomarkers, cardiac injury, and comorbidities associated with severe illness and mortality in coronavirus disease 2019 (COVID‐19): A systematic review and meta‐analysis

Abstract: Aims To explore the correlation between cardiac‐related comorbidities, cardiac biomarkers, acute myocardial injury, and severity level, outcomes in COVID‐19 patients. Method Pubmed, Web of Science, Embase, CNKI, VIP, Wanfang, Cochrane Library databases, medRxiv, and Sinomed were reviewed systemically. Various types of clinical research reporting cardiac‐related comorbidities, cardiac biomarkers including lactate dehydrogenase (LDH), troponin I (TnI), high sensitivity tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 76 publications
2
19
0
1
Order By: Relevance
“…Particularly, we found that several inflammatory, thrombotic, and hepatic biomarkers change their behavior in COVID-19. In agreement with current knowledge (Supplementary Table 4), well-known cardiovascular biomarkers such as ultrasensitive troponin (Zhu et al, 2021), C-reactive protein, and lactic dehydrogenase were increased in the groups with fatal outcome (Supplementary Table 4). Our work reinforces the role of other less well identified biomarkers such as hepatic features (Ramos-Lopez et al, 2021) and pulmonary artery diameters (Spagnolo et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Particularly, we found that several inflammatory, thrombotic, and hepatic biomarkers change their behavior in COVID-19. In agreement with current knowledge (Supplementary Table 4), well-known cardiovascular biomarkers such as ultrasensitive troponin (Zhu et al, 2021), C-reactive protein, and lactic dehydrogenase were increased in the groups with fatal outcome (Supplementary Table 4). Our work reinforces the role of other less well identified biomarkers such as hepatic features (Ramos-Lopez et al, 2021) and pulmonary artery diameters (Spagnolo et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Cardiovascular manifestations of COVID-19 are frequently reported ( 2 , 40 ). Acute heart failure and exacerbation of chronic heart failure are reported in up to 20-30% of hospitalized patients, and carry high mortality rates, especially in patients with severe comorbidities ( 41 43 ). Acute coronary syndrome has been reported in a high proportion of patients, probably because of plaque rupture, coronary spasm, or microthrombi triggered by systemic inflammation and cytokine storm ( 44 ).…”
Section: Diagnostic and Prognostic Value Of Biomarkersmentioning
confidence: 99%
“…The prognostic value of hs-cTn in COVID-19 has been consistently shown in multiple, different study populations across the globe and was confirmed by data from several metaanalyses [39][40][41][42]. One of the more recent ones reported a significant association between COVID-19 disease severity and levels of cardiac troponin from pooled patient data of 28 studies comprising 7812 cases.…”
Section: Biomarkers Of Myocyte Injury 21 High-sensitive Cardiac Tropo...mentioning
confidence: 66%